1983
DOI: 10.1177/00220345830620031201
|View full text |Cite
|
Sign up to set email alerts
|

Post-irradiation Polymerization of Visible Light-activated Composite Resin

Abstract: The rate of post-exposure polymerization and the effects of initial polymerization on the final polymerization of visible lightactivated composite resin were studied. The extent of polymerization, as indicated by hardness values, was influenced by the exposure time to the photo-activating radiation and by the postexposure time. The timing of testing is critical when studying the properties of visible light-activated composite resins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
5

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 5 publications
4
63
0
5
Order By: Relevance
“…12,13 In our study, the microhardness of the celluloid strip-finished composite sur- face increased more progressively. The finding is in partial agreement with the observation of Helvatjoglou et al, 3 who reported a progressive increase of microhardness of the celluloid strip-finished composite surface at 4 weeks.…”
Section: Discussionsupporting
confidence: 50%
“…12,13 In our study, the microhardness of the celluloid strip-finished composite sur- face increased more progressively. The finding is in partial agreement with the observation of Helvatjoglou et al, 3 who reported a progressive increase of microhardness of the celluloid strip-finished composite surface at 4 weeks.…”
Section: Discussionsupporting
confidence: 50%
“…Hardness is a surface property defined as the resistance of a material to permanent indentation or penetration. The composite's surface hardness and the effect of post-irradiation aging have been studied extensively by many investigators [12][13][14] . It has been reported that the hardness of inorganic fillers has a direct effect on the material's hardness 15 .…”
Section: Introductionmentioning
confidence: 99%
“…There are discrepancies in outcomes of previous reports concerning the polymerization kinetics after light-curing of RBCs. Hansen 18 found that the most of the polymerization reaction takes place during the first minutes after irradiation or one hour after removal of the irradiation source, while Leung et al, 19 reported that a significant portion of reaction may occur during the first 24 h. Moreover, in a recent study it has been reported a further increase in microhardness of 50-80% of the immediate readings for some RBC materials in room temperature after 168 h 20 . The extent of post-irradiation polymerization may be influenced by various intrinsic factors such as monomer composition, availability of free radicals and initial degree of conversion.…”
mentioning
confidence: 97%